Effects of dredging on critical ecological processes for marine invertebrates, seagrasses and macroalgae, and the potential for management with environmental windows using Western Australia as a case study. (July 2017) - Fraser, Matthew W.; Short, Jessie; Kendrick, Gary; McLean, Dianne; Keesing, John; Byrne, Maria; Caley, M. Julian; Clarke, Doug; Davis, Andrew R.; Erftemeijer, Paul L.A.; Field, Stuart; Gustin-Craig, Sam; et al.
Highlights: Avoiding or reducing dredging during sensitive life history periods may help to minimize dredging impacts. Selection and management of Environmental Windows (EWs) relies on accurate species- and location-specific information. Large knowledge gaps exist for life histories of benthic marine organisms in Western Australia (WA). The timing of known critical life stages of different species in WA shows large temporal and spatial variation. EWs are best considered on a location-specific basis for ecologically important species for which sufficient knowledge exists. Abstract: Dredging can have significant impacts on benthic marine organisms through mechanisms such as sedimentation and reduction in light availability as a result of increased suspension of sediments. Phototrophic marine organisms and those with limited mobility are particularly at risk from the effects of dredging. The potential impacts of dredging on benthic species depend on biological processes including feeding mechanism, mobility, life history characteristics (LHCs), stage of development and environmental conditions. Environmental windows (EWs) are a management technique in which dredging activities are permitted during specific periods throughout the year; avoiding periods of increased vulnerability for particular organisms in specific locations. In this review we identify these critical ecological processes for temperate and tropical marine benthic organisms; and examine if EWs could be used to mitigate dredging impacts using Western Australia (WA) as a case study. We examined LHCs for a range of marine taxa and identified, where possible, their vulnerability to dredging. Large gaps in knowledge exist for the timing of LHCs for major species of marine invertebrates, seagrasses and macroalgae, increasing uncertainty around their vulnerability to an increase in suspended sediments or light attenuation. We conclude that there is currently insufficient scientific basis to justify the adoption of generic EWs for dredging operations in WA for any group of organisms other than corals and possibly for temperate seagrasses. This is due to; 1) the temporal and spatial variation in the timing of known critical life history stages of different species; and 2) our current level of knowledge and understanding of the critical life history stages and characteristics for most taxa and for most areas being largely inadequate to justify any meaningful EW selection. As such, we suggest that EWs are only considered on a case-by-case basis to protect ecologically or economically important species for which sufficient location-specific information is available, with consideration of probable exposures associated with a given mode of dredging.